Efficacy and safety of ombitasvir/paritaprevir/ritonavir/ribavirin in management of Egyptian chronic hepatitis C virus patients with chronic kidney disease: A real-life experience. Issue 42 (16th October 2020) - Abd-Elsalam, Sherief; Abo-Amer, Yousry Esam-Eldin; El-Abgeegy, Mohamed; Elshweikh, Samah A.; Elsergany, Heba Fadl; Ahmed, Rehab; Elkadeem, Mahmoud; Hawash, Nehad; Soliman, Shaimaa; Badawi, Rehab; Elguindy, Ayman Mohammed Abdou; Soliman, Moataz Yousry; et al.
Abstract : Abstract: Treatment of hepatitis C virus (HCV) infection in patients with chronic kidney disease was difficult in the past because of the use of interferon (IFN). It was associated with high risk IFN-related adverse reactions due to reduced renal clearance of IFN. This study aimed to evaluate the antiviral efficacy, safety, and tolerability of ombitasvir/paritaprevir/ritonavir/ribavirin in chronic kidney disease patients infected with chronic HCV. This observational, open-label prospective study was carried out on 103 patients infected chronic HCV with different grades of renal impairment. Paritaprevir/ritonavir and ombitasvir (75/50/12.5 mg) twice daily plus ribavirin were given to the patients for 12 weeks. Dose adjustment of ribavirin was done according to degree of renal impairment. Sustained virological response (12 weeks after the end of treatment) occurred in 101 patients (98.1%). Anemia occurred in 48 patients. No serious adverse events were observed in any patient. Paritaprevir/ritonavir and ombitasvir plus ribavirin for 12 weeks was considered to be safe and effective in the treatment of chronic HCV infected patients with varying degrees of renal impairment.